Genetic diversity of Plasmodium malariae in sub-Saharan Africa: a two-marker genotyping approach for molecular epidemiological studies - Rodi, Miriam; Kawecka, Katarzyna; Stephan, Laura; Berner, Lilith; Medina, Martha Salinas; Lalremruata, Albert; Woldearegai, Tamirat Gebru; Matsiegui, Pierre Blaise; Groger, Mirjam; Manego, Rella Zoleko; Ekoka Mbassi, Dorothea; Mombo-Ngoma, Ghyslain; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPlasmodium malariae is the most common non-falciparum species in sub-Saharan Africa. Despite this, data on its genetic diversity is scarce. Therefore, we aimed to establish a P. malariae genotyping approach based on size polymorphic regions that can be easily applied in molecular epidemiological studies.MethodsFour potential genotyping markers, Pm02, Pm09, P. malariae thrombospondin-related anonymous protein (pmtrap), and P. malariae merozoite surface protein fragment 2 (pmmsp1 F2) were amplified via nested PCR and analysed using automated capillary gel electrophoresis.ResultsWe observed the highest allelic diversity for pmtrap (MOI = 1.61) and pmmsp1 F2 (He = 0.81). Further applying the two markers pmtrap and pmmsp1 F2 on a different sample set of 21 P. malariae positive individuals followed up over one week, we saw a high consistency in their performance. The results show a large complexity and high dynamics of P. malariae infections in the asymptomatic Gabonese study population.DiscussionWe successfully implemented a new genotyping panel for P. malariae consisting of only two markers: pmtrap and pmmsp1 F2. It can be easily applied in other settings to investigate the genotype diversity of P. malariae populations, providing further important data on the molecular epidemiology of this parasite species.